Hug tent: A caring methodology guided by affection (Research, Society and Development, 2021)
The present work has as main objective to present the Tent of Hug as a systematized care methodology within the scope of Integrative and Complementary Practices in Health, within an approach of Integrative Playful Experiences. It is a qualitative method research, an existential action research was carried out. The target audience was 48 students from the Faculty of Nursing - FAEN of the State University of Rio Grande do Norte - UERN. The hug tent is an itinerant care methodology that highlights the need to cultivate new perspectives for oneself and for the other, providing opportunities for care, listening, speaking and touching. Through a non-cast script in which the subjects have the possibility to take care of themselves and realize the need to care for others, with the PICS apparatus. The Tent of Embrace goes through four main stages: affective reception; weaving knowledge; connections and reflections; cooperation and self-care. Tenda do Abraço was presented as a humanescent, systematic and powerful care methodology for connection with oneself and with the other, improving the quality of interpersonal interactions among university students.